Advances in Evaluating Fluid Levels: Bioimpedance in Patients with Kidney Failure - Harith Abdelkareem Baker; Mohammed Sabah Jarjees; Amer Farhan Sheet; Thair Hawas Hamed (NTU Journal of Engineering and Technology)
This study delves deeply into the various facets of bioimpedance analysis as it relates to the development of chronic kidney disease (CKD). The use of bioimpedance spectroscopy (BIS) to evaluate the effectiveness of peritoneal dialysis (PD) and determine dialysis adequacy using variables like volume (V) and Kt/V is at the heart of this compilation. The investigations closely look at how important water distribution is for the advancement of CKD and how that affects patient outcomes. Evaluation of several body composition measurement methods is emphasized, especially the combination of the bioelectrical impedance analysis (BIA) ratio and the dry mass index (DMI). By applying the BIA TBW Watson ratio, these approaches provide important insights into the relationships between fluid volume and physiological indicators, such as body mass index (BMI) and total body water (TBW). The study emphasizes the differences in fluid overload diagnosis between conventional clinical assessments and sophisticated bioimpedance techniques, particularly in older patients with chronic kidney disease (CKD), underscoring the need for proper monitoring and intervention.